Energy Production and Utilization in the Context of Tocantins Agribusiness: An Approach Based on Science, Technology and Society Relations for Technical High School (Research, Society and Development, 2020)
This paper aims to investigate the articulation between the concept of energy and social and environmental issues within the context of agribusiness in the state of Tocantins, belonging to the Brazilian Midwest region, with emphasis on Science, Technology and Society (CTS) relations, supported by a set of didactic and pedagogical interventions. The research subjects were students of the 3rd year of High School Integrated to Technical Education in Administration and Agribusiness of the Federal Institute of Education, Science and Technology of Tocantins (IFTO) - Campus Palmas. Teaching strategies such as reading and discussion of texts, presentation of videos and PowerPoint, experimental activities in the laboratory, and technical visit to a solar plant belonging to the institution were used. As a result of this research, we found that despite the challenges inherent in the CTS approach, it can offer a better-quality education, integrated and close to the reality and expectation of students, allowing us to understand that learning in physics goes far beyond its basic contents. The proposal enabled students to adopt a more critical, reflective stance and the development of values and attitudes related to social and environmental issues, as well as a commitment to learning for life and the exercise of citizenship.